Genetic diversity and relationship among North East Hill (NEH) goats - SHIVAHRE, PUSHP RAJ; VERMA, N K; AGGARWAL, R A K; SHARMA, REKHA; DIXIT, S P; SAVINO, N (The Indian Journal of Animal Sciences, 2019)
Genetic diversity and relationship among three goat populations i.e. Singharey, Sikkim Black goat and Long hair Nagaland goat also known as Sumi-Ne of North eastern hill region. Fifty blood samples were studied from each population and tested with a battery of 25 and satellite markers. Number of alleles observed was 116 (Sumi- Ne), 182 (Singharey) and 124 (Sikkim Black). Average numbers of alleles observed were 5.04±0.38 (Sumi-Ne), 7.91 ±0.57 (Singharey) and 5.39±0.30 (Sikkim black goats) and average effective numbers were 2.57 ±0.28, 3.49±0.32 and 2.77±1.68, respectively. Singharey had relatively more private alleles but with comparatively lower frequency. The average observed and expected heterozygosity was 0.34±0.04 and 0.49±0.05 in Nagaland goats, 0.50±0.04 and 0.64±0.03 in Singharey and 0.42±0.33 and 0.57±0.40 in Sikkim black goats. Average FIS, FIT, FST were 0.27±0.04, 0.39±0.03, 0.15±0.03, respectively. All the three populations showed absence of bottleneck (reduction in effective population size. Analysis of molecular variance revealed that 39% of the total genetic diversity existed among the individuals within populations and only 18% of the total genetic diversity accounted for differences among populations. Sumi-Ne showed similar genetic distance (0.636) from the Singharey and Sikkim Black goat, whereas, Singharey and Sikkim Black were genetically close. Compared to other Indian goat breeds, all the three NEH populations were far distanced from Berari, Black Bengal, Bundelkhandi, Ganjam, Jharkhand Black, Konkan Kanyal and Kutchi. In the neighbour joining diagram the three goat populations were plotted separately. Considering the geographical and genetic identity of NEH goats, conservation and improvement programmes may be formulated accordingly.